ATRIAL FIBRILLATION IN CARDIOVASCULAR INTERVENTIONS IN ON-PUMP AND OFF-PUMP REGIMENS - O. A. Rubanenko; O. V. Fatenkov; S. M. Khokhlunov (Российский кардиологический журнал)
Aim. To evaluate the prevalence of post-operation atrial fibrillation (POAF) in coronary artery bypass (CBG) on-pump or off-pump regimens.Material and methods. Totally, 469 patients studied with ischemic heart disease admitted for CBG (389 patients, 77% — males, mean age — 61,1±8,0 y.) had onpump CBG, and 2nd group — off-pump (80 patients, 80% — males, mean age — 58,4±8,0 y.).Results. In early post-operation period AF developed in 17,7% of patients in the 1st group, in 7,5% in the 2nd. Multifactor analysis showed the odds ratio for the aorta clumping time more than 36 mins as 1,8 (95% CI, 1,0-3,3, р=0,04), for ischemia time more than 19 mins — 2,0 (95% CI, 1,1-3,8, р=0,02), for the age more than 59 y. — 2,7 (95% CI, 1,5-5,0, р=0,001), for the front-back size of the left atrium more than 39 mm — 3,7 (95% CI, 2,1-6,4, р<0,0001), for the LVEF less than 55% — 1,8 (95% CI, 1,1-3,2, р=0,03). However the odds ratio for cardiopulmonary bypass more than 56 mins was 1,4 (95% CI, 0, 6-3,1, р=0,4) and “p” value got non-significant.Conclusion. In our study we showed higher prevalence of POAF in CBG as on-pump comparing to off-pump regimen. The most valuable parameter predetermining arrhythmia development were age, front-back size of the left atrium, LVEF, duration of aorta clumping and duration of ischemia